Leadership Style and Interpersonal Communication of Employee Satisfaction and It’s Effect on The Employee Performance - Rifqi Amri Putri (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This study aims to determine the relationship between leadership style, interpersonal communication to employee job satisfaction and its effect on employee performance. The method used in this study is path analysis with SPSS application version 21. These results indicate that the relationship of leadership style on employee job satisfaction has a contribution of 0.24, while the relationship between leadership style on the performance of employees have a contribution of 0.279. In addition, the relationship between interpersonal communication on employee job satisfaction has a contribution of 0.131, whilst the relationship of interpersonal communication on the employee's performance has contributed of 0.448. The employee satisfaction relationship to employee performance has a contribution of 0.185. As for the total effect of leadership style through employee satisfaction on the performance of employees have a contribution of 0.323 and the total effect of interpersonal communication through employee satisfaction to employee performance has contributed 0.472.